(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2025)
The paper examines the tourism entrepreneurship in Nepal’s Kathmandu Valley, focusing on three case studies. The paper has followed a qualitative research design to analyse the data gathered through case studies. It highlights the importance of education, resource management, innovation, and family support in entrepreneurship. The study highlights the integration of Newa (Newari) ethnic cuisine with modern culinary practices, the resilience of entrepreneurs, family support, and cultural alignment. It also highlights the need for robust policies supporting education, vocational training, financial incentives, and networking platforms. The study also suggests promoting cultural preservation, addressing systemic barriers, and encouraging public-private collaboration to enhance the tourism ecosystem. These insights provide a foundation for stakeholders to create a supportive environment for sustainable tourism entrepreneurship in Nepal.